The epidemiology of traumatic brain injuries within USA Fencing, 2015-2020: prevention, care, and return to play considerations - Thompson, A.; Summers, J.; Freedman, A. (British Journal of Sports Medicine, 2021)
Background Mild traumatic brain injury (mTBI) is an increasing sports-related and public health concern affecting millions annually. While competitive fencing has been identified as a safe sport with a low occurrence of sport related injury, prevention, care, and return to play considerations from a mTBI is a persisting issue due to sport related factors.